Jamaica : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper analyzes Jamaica's experience of low growth despite consistently high investment rates. It suggests that the link between public debt and productivity is part of the answer to the puzzle. The paper considers Jamaica's debt management strategy and its optimal debt structure. It also reviews the institutional framework for debt management in Jamaica, and presents a newly constructed dataset that documents Jamaica's notable market access to long-maturity, fixed interest rate, and domestic currency bond placements.